Effect of cigarette smoking on serum anti-Mullerian hormone and antral follicle count in women seeking fertility treatment: a prospective cross-sectional study - Ganesh Acharya; Roy Homburg; Amit Shah; Anil Gudi; Priya Bhide; Elizabeth Timlick; Abhijit Kulkarni (BMJ Open, 2022)
Objectives The relationship between smoking and ovarian reserve markers is inconclusive. The primary objective of our study was to assess the effect of cigarette smoking on the quantitative ovarian reserve parameters, serum anti-Mullerian hormone (AMH) and antral follicle count (AFC) as relevant to prediction of fertility outcomes in women seeking fertility treatment. Our secondary aims were to validate self-reported smoking behaviour using biomarkers and evaluate the association between biomarkers of ovarian reserve (serum AMH and AFC) with biomarkers of smoking exposure (breath carbon monoxide (CO) and urine cotinine levels).Design Prospective, cross-sectional study.Setting Single tertiary care fertility centre.Participants Women ≤35 years seeking fertility treatment.Primary outcome measures Serum AMH and AFC.Results Significant differences were found among current smokers, ex-smokers and never smokers for breath CO (F(2,97)=33.32, p<0.0001) and urine cotinine levels (p<0.001). However, no significant differences were found either for serum AMH (F(2,91)=1.19, p=0.309) or total AFC (F(2,81)=0.403, p=0.670) among the three groups. There was no significant correlation between pack years of smoking and serum AMH (r=−0.212, n=23, p=0.166) or total AFC (r=−0.276, n=19, p=0.126). No significant correlation was demonstrated between breath CO and serum AMH (r=0.082, n=94, p=0.216) or total AFC (r=0.096, n=83, p=0.195). Similarly, no significant correlation was demonstrated between urine cotinine levels and serum AMH (r=0.146, n=83, p=0.095) or total AFC (r=−0.027, n=77, p=0.386).Conclusion We did not find a statistically significant difference in quantitative ovarian reserve markers between current smokers, ex-smokers and never smokers which would be clinically meaningful in our study population. We confirmed that self-reported smoking correlates well with quantitatively measured biomarkers of smoking. This validated the self-reported comparison groups to ensure a valid comparison of outcome measures. There was no significant association between biomarkers of smoking and biomarkers of ovarian reserve. We were also unable to demonstrate a correlation between the lifetime smoking exposure and ovarian reserve.